2013
DOI: 10.1016/j.mce.2013.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Nonhuman primate models of polycystic ovary syndrome

Abstract: With close genomic and phenotypic similarity to humans, nonhuman primate models provide comprehensive epigenetic mimics of polycystic ovary syndrome (PCOS), suggesting early life targeting for prevention. Fetal exposure to testosterone (T), of all nonhuman primate emulations, provides the closest PCOS-like phenotypes, with early-to-mid gestation T-exposed female rhesus monkeys exhibiting adult reproductive, endocrinological and metabolic dysfunctional traits that are co-pathologies of PCOS. Late gestational T … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
62
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(67 citation statements)
references
References 112 publications
4
62
1
Order By: Relevance
“…Animal studies suggest that high maternal androgen concentrations during gestation result in PCOS-like phenotypes, in primates (14,15,34), sheep (35) and rodents (36). Especially studies by Abbott (13,14,15,34,37), in prenatally exposed rhesus monkeys, have strongly encouraged the hypothesis that the intra-uterine exposure to androgens can cause clinical and biochemical features of PCOS in later life, though these androgen concentrations are supraphysiological.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Animal studies suggest that high maternal androgen concentrations during gestation result in PCOS-like phenotypes, in primates (14,15,34), sheep (35) and rodents (36). Especially studies by Abbott (13,14,15,34,37), in prenatally exposed rhesus monkeys, have strongly encouraged the hypothesis that the intra-uterine exposure to androgens can cause clinical and biochemical features of PCOS in later life, though these androgen concentrations are supraphysiological.…”
Section: Discussionmentioning
confidence: 99%
“…Especially studies by Abbott (13,14,15,34,37), in prenatally exposed rhesus monkeys, have strongly encouraged the hypothesis that the intra-uterine exposure to androgens can cause clinical and biochemical features of PCOS in later life, though these androgen concentrations are supraphysiological.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Available studies do not support the concept that the common PCOS is due to a single-gene defect, although large association studies have suggested that a cluster of genes may increase the individual susceptibility to develop it (22,23). Animal studies have also suggested that fetal exposure to androgen excess may contribute to development of the PCOS phenotype later in time (24,25). These theories imply the potential direct role of intrauterine androgen excess in favoring the metabolic derangements, including hypertrophy of the visceral fat and associated insulin resistance coupled with compensatory hyperinsulinemia.…”
Section: Arguments In Favor Of the Definition Of Secondary Pcosmentioning
confidence: 99%
“…Supportive evidence includes that androgen excess from endogenous [congenital adrenal hyperplasia (6)] or exogenous [female-to-male transsexuals (7)] sources can produce polycystic ovaries. Furthermore, androgens induce reproductive, metabolic, and endocrine features of PCOS in rodent, sheep, and primate animal models of PCOS (8)(9)(10). As all androgen action is mediated via the androgen receptor (AR), AR-mediated actions are thereby strongly implicated in the development of PCOS.…”
mentioning
confidence: 99%